Pelatihan Model Pendekatan Deskriptif Analitik dalam Pembelajaran Sejarah Guru SMA N 11 Muaro Jambi - Budi Purnomo (Universitas Batanghari Jambi, 2022)
A history learning approach that emphasizes the teacher's ability to improvise (story) by highlighting facts without giving students opportunities for reflective activities about the facts presented. So the characteristics of history learning like this will be difficult to break free from the presentation orientation that smells extrinsic and minimize opportunities for developing learning capacity. This training aims to provide training to teachers of history subjects at SMA N 11 Muaro Jambi in applying the Analytical Descriptive Approach Model in history learning. This training uses a qualitative method that focuses on the process. This training resulted in the conclusion that the analytical history approach is to describe history in a systematic or structured manner. For this reason, the analytical history approach requires concepts and theories to explain these historical phenomena so that history has meaning and is relevant for today's interests.